(untitled) (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2015)
Monohalogenated acetic acids have been widely used in industry and agriculture as precursor to chemicals and as herbicides, respectively. Monobromoacetic acid (MBA) is a chemical intermediate for the manufacturing of various chemicals with application in agriculture and pharmacy. Bioremediation of monobromoacetic acid, has been touted as a more economical and feasible method compared to physical and chemical approaches. Previously, we model the growth of growth of Moraxella sp. B on monobromoacetic acid from published literature to obtain vital growth constants. We discovered that the Buchanan-three-phase model via nonlinear regression utilizing the least square method was the very best model to explain the growth curve. However, the use of statistical tests to choose the best model relies heavily on the residuals of the curve to be statistically robust. More often than not, the residuals must be tested for the presence of outliers (at 95 or 99% of confidence). In this work, the Grubb’s test to detect the presence of outlier in the growth model was carried out.